Analisis Faktor-faktor yang Mempengaruhi Keputusan Konsumen dalam Memilih Jasa Perbankan Syariah di Kota Padang - Yuanita, Ika; Nurhayati, Nurhayati (Jurnal Ekonomi, 2013)
The Development of Syariah Bangking in Indonesia was started by the implementation of UU No. 23 in 2009 as a dual banking systen. This research purpose are to identify the characteristic customer behaviour by their preference using services in Syariah Banking in Padang Munipacility. Then, to identify the influence factors of the purchasing decision by customer using services in Syariah Banking in Padang Munipacility. Research design is descriptive-correlational, samples are consist of 100 number of customer using service in Syariah Banking in Padang Munipacility. Research metode is using crosstabulation analysis by Chi-Square Correlation with Pearson and Odds Ration calculations. The empirical result shows customer behaviour that represent by culture, social, costumre sharacteristic or personality, and psychological factors are significant t determine purchasing decision of customer using in Syariah Banking in Padang Munipacility with level of significant at a=0,05. Culture and social factors had a positive correlation to purchasing decision, but customer personality and psycological factors has a negative correlation to purchasing decicion that replected by Pearson-R. Beside that culture factors still more important factors among others that replected by Odds Ratio of Purchasing decision to ude service in Syariah Banking in Padang Munipacility.